Lines of least resistance and genetic architecture of house mouse (Mus musculus) mandible shape. Issue 3 (23rd April 2013) - Boell, Louis
SUMMARY Evolution along "lines of least resistance (LLR)" is a well‐established phenomenon, which is ultimately based on variational properties of the developmental system. However, it has remained unclear which aspects of development are responsible for observed distributions of variation. This article suggests that house mouse mandible shape may present an opportunity for future research in this field. The genetic architecture of mouse mandible shape has been investigated in the laboratory, and its evolution has been surveyed in studies on natural variation. Here, I ask whether evolutionary diversification of mandible shape follows "LLR" by comparing principal directions of genetic and evolutionary variation, and I assess the potential contribution of specific genomic regions to evolutionary divergence along these directions. The role of two aspects of development, QTL number (presumably reflecting mutational target size) and canalization, is comparatively assessed. Overall, our results demonstrate a strong tendency of genetic and evolutionary systems to vary along similar directions, suggesting that mandible shape evolves along LLR at the level of populations, subspecies and species. At the level of genetic factors, effects bearing similarity to directions of evolution are significantly overrepresented, providing support for the mutational target size hypothesis. A role for canalization is not supported by a clear correlation between directions of evolution and size of genetic effects; however, the evidence for canalization remains ambiguous. These results provide some insights into how the developmental system may shape the variational properties of genetic systems and thus influence the direction of evolution.